2021
DOI: 10.1111/eos.12768
|View full text |Cite
|
Sign up to set email alerts
|

Bond durability of universal adhesives to intact enamel surface in different etching modes

Abstract: This study aimed at determining the enamel bond durability of universal adhesives to intact enamel (IE) and ground enamel (GE) in different etching modes under thermal cycling (TC) and fatigue stresses. Two universal adhesives and a two‐step self‐etch adhesive were used. Enamel specimens were divided into four groups by treatment: (i) GE in etch‐and‐rinse, (ii) IE in etch‐and‐rinse, (iii) GE in self‐etch, and (iv) IE in self‐etch. Bonded specimens were subjected to TC, and then shear bond strengths (SBS) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…Most of the application groups and adhesive systems demonstrated significantly higher SBS values in the ER mode than in the SE mode. This was in line with previous studies, which showed that phosphoric acid pre-etching before the application of a primer contributes to enhanced immediate and durable enamel bond performance [25,26]. However, none of the adhesives in Group III after TC showed any significant differences in SBS between the ER and SE modes, apart from GU at TC 10,000.…”
Section: Discussionsupporting
confidence: 91%
“…Most of the application groups and adhesive systems demonstrated significantly higher SBS values in the ER mode than in the SE mode. This was in line with previous studies, which showed that phosphoric acid pre-etching before the application of a primer contributes to enhanced immediate and durable enamel bond performance [25,26]. However, none of the adhesives in Group III after TC showed any significant differences in SBS between the ER and SE modes, apart from GU at TC 10,000.…”
Section: Discussionsupporting
confidence: 91%
“…Adhesives with silane (PBE and TUB) or without silane (iBOND and AEB) demonstrated comparable TBS in the young and old groups regardless of the silane level. These results concur with those of Moritake et al, [15] Suzuki et al, [25], and Ouchi et al [17] The stability of silane may be harmed by the acidic pH of PBE and TUB, leading to a changed chemical formula with a decreased priming capability.…”
Section: Discussionsupporting
confidence: 91%
“…After establishing these basic principles, the research group extended fatigue bond strength evaluations to cover many factors with an influence on tooth bonding, such as the influence of acidic functional monomers [34] , double coating [35] , the oxygen inhibition layer [36] , [37] , shortened application times of adhesive systems [38] , the etching mode for universal adhesives [39] , [40] , [41] , application of different etching agents [42] , [43] , [44] , [45] , silver diamine fluoride pre-treatment [46] , the prismatic structure of enamel [47] , surface moisture [48] or smear layer of substrates [49] , the use of different adhesive systems [50] , [51] , phosphoric acid pre-etching [52] , [53] , [54] , self-adhesive restorative materials [55] , short fiber resin composites [56] , and water storage of specimens [57] . These evaluations did provide new insights, but also raised methodological suggestions and questions from researchers.…”
Section: Standardization Of Test Conditionsmentioning
confidence: 99%